2014
DOI: 10.2319/072314-515.1
|View full text |Cite
|
Sign up to set email alerts
|

Interproximal reduction of teeth: Differences in perspective between orthodontists and dentists

Abstract: Objective: To determine if interproximal reduction of teeth (IPR) is perceived differently by orthodontists and general dentists. Materials and Methods: A Web-based survey containing statements about IPR was developed and randomly distributed to orthodontists and general dentists. Results: The majority of orthodontists and general dentists strongly agreed that IPR is a minimally invasive procedure that poses little risk for the development of interproximal decay. However, general dentists were more likely to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…It removes about 0.5 mm outer enamel on the interproximal surfaces of teeth 2) . A recent study found that 46% of the general dentists and 67% of the orthodontists routinely performed IPR 3) . However, the IPR procedures leave various grooves and furrows on enamel leading to a significantly increased surface roughness 4,5) , and these furrows can still be clearly visible even one year later 6) .…”
Section: Introductionmentioning
confidence: 99%
“…It removes about 0.5 mm outer enamel on the interproximal surfaces of teeth 2) . A recent study found that 46% of the general dentists and 67% of the orthodontists routinely performed IPR 3) . However, the IPR procedures leave various grooves and furrows on enamel leading to a significantly increased surface roughness 4,5) , and these furrows can still be clearly visible even one year later 6) .…”
Section: Introductionmentioning
confidence: 99%
“…6 The advantages of IPR are decreased treatment time, prevention of interdental gingival retraction, and less tooth movement. 10 IPR can also create space for better alignment, minimize potential problems with extraction therapy, and thus allow self-retention. 6,10 IPR should not be carried out in patients with a high risk for caries and in those with poor oral hygiene to avoid the risk of development of caries.…”
Section: Discussionmentioning
confidence: 99%
“…16 Beberapa metode dari prosedur ini adalah : (1) air rotor stripping menggunakan bor diamond atau bor tungsten-carbide yang halus, (2) diamond-coated stripping disk atau (3) strip abrasive yang dapat dikendalikan dengan tangan atau menggunakan mesin. 4,19 Indikasi dari perawatan reduksi interproksimal adalah untuk pasien dengan kebersihan mulut yang baik, maloklusi kelas I dengan arch-length discrepancies dengan profil ortognati, kelas II dengan crowding ringan atau pasien yang memiliki diskrepansi ukuran gigi Bolton. 14,20 Crowding pada insisif rahang bawah, untuk reshaping gigi dengan bentuk kurang baik, memperbaiki kontur gingival dengan menghilangkan ruangan berbentuk segitiga pada papilla interdental, dan untuk mengkoreksi kurva spee.…”
Section: Pembahasanunclassified